Intratumoral neutrophil-to-lymphocyte ratio is mirrored by circulating neutrophil-to-lymphocyte ratio in non-small cell lung cancer - Jing Wang; Ignacio I Wistuba; Alexandre Reuben; Chantale Bernatchez; Tina Cascone; Jianjun Zhang; Boris Sepesi; Ara A Vaporciyan; Marcelo V Negrao; Hai T Tran; Lorenzo Federico; Mara B Antonoff; et al. (Journal for ImmunoTherapy of Cancer)
Tumor-initiated emergency granulopoiesis results in expansion of the circulating neutrophil compartment and neutrophil recruitment into the tumor microenvironment (TME), which may in turn promote tumor progression. Although an elevated circulating neutrophil-to-lymphocyte ratio (cNLR) has repeatedly been demonstrated to be an adverse prognostic factor in patients with non-small cell lung cancer (NSCLC), whether this neutrophil expansion in circulation reflects a similar relative neutrophil abundance in the TME remains unclear. We sought to characterize the relationships between cNLR and the intratumoral neutrophil-to-lymphocyte ratio (tNLR), between tNLR and proteogenomic and immune features of NSCLC tumors, and between tNLR and prognosis.We analyzed tNLR (transcriptomic signatures) and cNLR in a prospectively-enrolled cohort of patients with NSCLC (stage IA-III) that was subjected to multifaceted immunoprofiling (ImmunogenomiC prOfiling of early-stage Non-small cell lung cancer (ICON), N=150). We examined the relationship between tNLR and genomic, transcriptomic, and proteomic features of NSCLC tumors in The Cancer Genome Atlas (TCGA) and ICON. Finally, tNLR was analyzed for associations with postoperative recurrence-free survival (ICON) and overall survival (TCGA).In the ICON cohort, tNLR was significantly positively correlated with cNLR, but there was no association between intratumoral and circulating neutrophils or lymphocytes alone. High tNLR was associated with poor postoperative recurrence-free survival, and multivariate analysis indicated tNLR was a stronger driver of outcomes than cNLR. Mutations in KEAP1, STK11, PTEN, PI3K, and TSC2 were associated with an increased tNLR. Tumors with elevated tNLR were marked by proteomic and transcriptomic features indicative of increased cell cycle, receptor tyrosine kinase, and YAP signaling, as well as immunosuppression (reduced IFNG and GZMB expression). Flow cytometry and multiplex immunofluorescence confirmed reduced CD8+granzyme B+ T cells in the TME of tumors with high tNLR. Finally, TCGA confirmed associations between tNLR with prognosis, mutational status, and proteomic/transcriptomic features, and further showed that tNLR is prognostically relevant in multiple solid cancers.tNLR is mirrored by NLR in circulation (cNLR) in NSCLCs. High tNLR is associated with an immunosuppressed TME phenotype and poor prognosis across multiple cancers. These findings support ongoing investigations of the utility of cNLR and tNLR as clinical biomarkers in the context of patients with NSCLC treated with immune checkpoint inhibitor therapies.